Potassium Channel Conductance Is Involved in Phenylephrine-Induced Spontaneous Firing of Serotonergic Neurons in the Dorsal Raphe Nucleus - Wang, Jing; Wang, Yingzi; Du, Xiaona; Zhang, Hailin (Frontiers in Cellular Neuroscience, 2022)
The serotonergic (5-HT) network from the dorsal raphe nucleus (DRN) of the brain has been demonstrated to regulate cognition, emotion, and behaviors, including learning and the sleep-wake cycle. Dysregulation of the activity of 5-HT neurons in the DRN is thought to play an important role in emotional disorders. The activity of 5-HT neurons is regulated by norepinephrine (NE) released from the projection terminals of noradrenergic input from the locus coeruleus (LC) via activation of the α1-adrenoceptor. However, insight into the molecular mechanism underlying this NE-induced regulation of 5-HT neuron activity is not clear. In this study, using the agonist of α1-adrenoceptor phenylephrine (PE), brain slices, and patch clamp, we found that A-type, Kv7/KCNQ, and calcium-activated low-conductance K+ channels (SK) underlie PE-induced spontaneous firing in DRN 5-HT neurons. Using single-cell PCR and immunofluorescence, we also identified the isoforms of these K+ channel families that might contribute to the NE/PE-induced spontaneous firing of DRN 5-HT neurons.